Legal Action Against Of Notary Supervisory Board Decision - Erwin Asmadi (NOMOI Law Review, 2020)
The Notary Supervisory Board has the authority to supervise the Notary Public and in order to carry out this authority the Notary Supervisory Board issues decisions related to violations committed by Notaries. The method used is secondary data sourced from primary, secondary and tertiary legal materials. The decision of the Notary Supervisory Board for the central level is final and binding. If then there are parties who are not satisfied with the decision of the Notary Supervisory Board, what legal remedies can be taken by the dissatisfied party. Based on the research conducted, the decision of the Notary Supervisory Board can be categorized as a state administration decision which is a competency of the Administrative Court to examine, hear, and decide upon it. Therefore, if there are parties who are dissatisfied with the decision of the Notary Supervisory Board, then they can submit legal remedies to the Administrative Court.Keywords: Decision, Notary Supervisory Board, Administrative Court